Comprehensive analysis of a pyroptosis-related gene signature of clinical and biological values in spinal cord injury - Zhang, Pingping; Zhang, Jianping; Kou, Wenjuan; Gu, Guangjin; Zhang, Yaning; Shi, Weihan; Chu, Pengcheng; Liang, Dachuan; Sun, Guangwei; Shang, Jun (Frontiers in Neurology, 2023)
Background: Since some of the clinical examinations are not suitable for patients with severe spinal cord injury (SCI), blood biomarkers have been reported to reflect the severity of SCI. The objective of this study was to screen out the potential biomarkers associated with diagnosis of SCI by bioinformatics analysis. Methods: The microarray expression profiles of SCI were obtained from the Gene Expression Omnibus(GEO) database. Core genes correlated to pyroptosis were obtained by crossing the differential genes and module genes obtained by WGCNA analysis and lasso regression. The immune infiltration analysis and GSEA analysis revealed the essential effect of immune cells in the progression of SCI. In addition, the accuracy of the biomarkers in diagnosing SCI was subsequently evaluated and verified using the receiver operating characteristic curve (ROC) and qRT-PCR. Results: A total of 423 DEGs were identified, among which 319 genes were up-regulated and 104 genes were down-regulated. Based on WGCNA analysis, 6 potential biomarkers were screened out, including LIN7A, FCGR1A, FGD4, GPR27, BLOC1S1 and GALNT4. The results of ROC curves demonstrated the accurate value of biomarkers related to SCI. The immune infiltration analysis and GSEA analysis revealed the essential effect of immune cells in the progression of SCI, including macrophage, natural killer cell, neutrophil and so on. The qRT-PCR results verified that FGD4, FCAR1A and LIN7A were significantly up-regulated in SCI patients. Conclusion: In this study, we identified and verified 3 immune pyroptosis-related hub genes by WGCNA and biological experiment. It is expected that the 3 identified potential biomarkers in peripheral white blood cells may provide a novel strategy for early diagnosis.